Value of strong ties to disconnected others: Examining knowledge creation in biomedicine - McFadyen, M. Ann; Semadeni, Matthew; Cannella, Albert A (Organization science (Providence, R.I.), 2009)
Knowledge creation requires the combination and exchange of diverse and overlapping knowledge inputs as individuals interact with exchange partners to create new knowledge. In this study, we examine knowledge creation among university research scientists as a function of their professional (ego) networks—those others with whom they collaborate for the purpose of creating new knowledge. We propose that knowledge creation relies, in part, on two attributes of a researcher's professional network structure—average tie strength and ego network density—and we provide insights into how these attributes jointly affect knowledge creation. Our study of over 7,300 scientific publications by 177 research scientists working with more than 14,000 others over an 11-year period provides evidence that the relationship between a research scientist's professional network and knowledge creation depends on both ego network density and average tie strength. Our evidence suggests that both attributes affect knowledge creation. Moreover, average tie strength interacts with density to affect knowledge creation such that researchers who maintain mostly strong ties with research collaborators who themselves comprise a sparse network have the highest levels of new knowledge creation.